Leaching of rare earth elements with sulfuric acid from bastnasite ores - Stopić, Srećko R.; Friedrich, Bernd G. (Vojnotehnički glasnik / Military Technical Courier, 2018)
Dissolution of rare earth elements from bastnasite ores was studied using sulfuric acid at the atmospheric pressure. The one step strategy with sulfuric acid was studied further and the results showed that filtering difficulties do not happen for the chosen parameter combinations. Furthermore, the best parameter combinations were those with low temperatures and low acid concentrations. All in all, direct leaching is a simple process that uses the cheapest acid on the market and offers good leaching recoveries. Attention should be given to the formation of gel, especially when taking the process to the large scale, and the subsequent elimination of Ca from the leachate.
Keywords: rare earth elements; hydrometallurgy; bastnasite; sulfuric acid